Strategi Pengelolaan Kawasan Industri Cilegon Menuju Eco Industrial Park - Fatah Sulaiman; Asep Saefuddin; Alinda FM Zain (The Institute for Research and Community Services, Institut Teknologi Bandung, 2008)
The purpose of this study is to formulate strategies and to develop appropriate scenario for the management of an industrial area towards Eco Industrial Park. Analytical Hierarchy Process (AHP) is used as the analytical method. Industrial actors in an industrial area can jointly improve environmental, economic, and social performance, through the minimization of environmental impact and also has the ability to make products with competitive advantage in the market, based on the results of gap analysis between existing conditions and the ideal concept and Eco Industrial Park benchmarking. The analysis and interviews with several experts showed that, in the industrial estate management of the Eco Industrial Park, the most important objective that needs be achieved is environmental and ecological sustainability.